Recent Advancements in Therapeutic Applications of Plant Based Green Synthesized Nanoparticles - Devi, S. Manju; Padma, A. Sai (Current Topics on Chemistry and Biochemistry Vol. 3, 2022)
The green synthesis of nanoparticles has gained wide attention in recent years due to their eco-friendly nature and cost-effectiveness. These nanoparticles are reported to exhibit various therapeutic functions with promising results. Though there are various biomaterials available for green synthesis, plants and plant products have proven as reliable sources for green synthesis with more cost-effectiveness and stability. As medicinal plants are well established for their potential therapeutic applications, the synthesis of nanoparticles using medicinal plants further enhances their properties. This chapter details various types of nanoparticles synthesized from different plant sources through green synthesis, emphasizing their therapeutic functions.